1994
DOI: 10.1016/0166-0934(94)90045-0
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for mapping and imitating viral B-cell epitopes

Abstract: Identification of viral B-cell epitopes is of importance in the selection of peptides for inclusion into subunit vaccines, the development of virus-specific serological tests and understanding the interaction of antibodies with viruses at a molecular level. B-cell epitopes can often be determined unequivocally by X-ray analyses of antibody-antigen complexes. This technique is, however, time-consuming and alternative strategies have now been developed for identifying epitopes. This article provides an overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Conformational epitopes consist of several amino acid residues that are discrete in the primary sequence but assemble to form an antigenic determinant on the tertiary structure of the native protein (3,17,23). Conformational epitopes are often formed from more than 10 residues separated from the primary structure (2,4,17). By Western blot analysis, MAb 15F3-1 detected NS1 very effectively in both native and denatured gels (data not shown) and the binding motif for 15F3-1 was located in residues 111 to 116 of the NS1 of DEN-1, indicating that the B-cell epitope of 15F3-1 is a linear epitope.…”
Section: Discussionmentioning
confidence: 99%
“…Conformational epitopes consist of several amino acid residues that are discrete in the primary sequence but assemble to form an antigenic determinant on the tertiary structure of the native protein (3,17,23). Conformational epitopes are often formed from more than 10 residues separated from the primary structure (2,4,17). By Western blot analysis, MAb 15F3-1 detected NS1 very effectively in both native and denatured gels (data not shown) and the binding motif for 15F3-1 was located in residues 111 to 116 of the NS1 of DEN-1, indicating that the B-cell epitope of 15F3-1 is a linear epitope.…”
Section: Discussionmentioning
confidence: 99%
“…However, a partial restoration of discontinuous epitopes in recombinant proteins during Western blotting may also contribute to their reactivity with MAbs (Harper et al, 1990). The incomplete expression of these epitopes in E. coli-expressed recombinant proteins was probably due to the lack of authentic higher-order structure, which is inherent to prokaryotic expression systems (Cason, 1994). Also, it cannot be ruled out that these discontinuous epitopes include residues located outside the identified regions of gBc.…”
mentioning
confidence: 93%
“…Previously, we showed that MAbs specific for discontinuous epitopes of gB retained reactivity against viral gB in a Western blot, although at a relatively low level, even after boiling the samples under reducing conditions before SDS-PAGE (Zaripov et al, 1998). Therefore, we expected that E. coli-expressed recombinant fragments, which presumably FDI lack authentic higher-order structure (Cason, 1994), could be used to map both continuous epitopes and the regions involved in the assembly of discontinuous epitopes. Fig.…”
mentioning
confidence: 99%
“…An appropriate identification of immunogenic motifs in antigens is the first fundamental step when designing epitope-based vaccines [ 30 ]. Advances in knowledge on B-cell epitope sequence and structure have been achieved by techniques such as nuclear magnetic resonance (NMR), and/or X-ray crystallography of antigen-antibody three-dimensional structure complexes [ 31 , 32 ], and by epitope mapping using predictive bioinformatic algorithms [ 33 ] and/or peptide library screening by antibody binding assays [ 34 , 35 , 36 ]. On the other hand, T-cell epitopes can be predicted by means of bioinformatic algorithms and experimentally characterized using MHC multimers and lymphoproliferation or ELISPOT assays [ 37 , 38 ].…”
Section: Overview Of Epitope-based Vaccinesmentioning
confidence: 99%